Penerapan Metode Pembelajaran Resitasi Dalam Meningkatkan Keaktifan Siswa Mata Pelajaran Al-Qur’an Hadis Siswa Kelas XI MA Swasta Jam’iyah Mahmudiyah Tanjung Pura - Zenny Fitriany A Fauzi T, Kamaliah, Nurmisdaramayani (CV. PUSDIKRA MITRA JAYA, 2023)
The purpose of this study is to find out the application of the recitation method to students of class XI MA Private MA Jam'iyah Mahmudiyah Tanjung Pura. To find out the activity of students in the subject of Al-Qur'an Hadith Students of class XI MA Private MA Jam'iyah Mahmudiyah Tanjung Pura. To find out the results of the activity of class XI MA Private MA Jam'iyah Mahmudiyah Tanjung Pura students in the Al-Qur'an Hadith subject after using the recitation method. The model in this study uses the Kurt Lewin research model which consists of 4 stages namely; planning, implementation of action, observation and reflection. The subject of this study was in class XI MAS Jam'iyah Mahmudiyah Tanjung Pura using the recitation learning method. Consisting of 26 students,. Data collection techniques using interviews, observation, documentation, and written test assessment. The results of the research on the initial test obtained the application of the recitation learning method to class X students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura with an average value of 64.73. With the number of students who completed as many as 10 (38.46%). In cycle I, an increase in student activity was obtained using the student recitation learning method with an average value of 69.23. With a total of 18 students (69.23%) who completed and an observation value of student activity of 87.5%, this shows an increase from the initial test both in terms of class average and learning completeness. In cycle II, an increase in student learning activity was obtained by using the recitation learning method with an average value of 76.73. We can see that the average value has increased from cycle I. The number of students who have completed is 24 (92.30%) and the student activity observation value is 95.83%. With the use of the recitation learning method there is a significant influence in increasing student activity in Al-Qur'an Hadith class XI MA Private MA Jam'iyah Mahmudiyah Tanjung Pura. The response of class XI students at Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura to the recitation learning method was very good with increasing scores from cycle I to cycle II. The response of class XI teachers at Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura to the recitation learning method was very good with increasing scores from cycle I to cycle II.